2018
DOI: 10.1016/j.chemphys.2018.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for competing proton-transfer and hydrogen-transfer reactions in the S1 state of indigo

Abstract: Indigo is a blue dye molecule that has been used since antiquity, although it is better known today for its use in blue jeans. Indigo has previously been shown to exhibit remarkable photostability due to fast excited state dynamics mediated by an excited state intramolecular proton transfer. Study of this process is complicated by the fact that the photophysics of indigo is very sensitive to the environment. In order to disentangle the intrinsic photodynamics of indigo from the effects contributed by the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The above proceeds efficiently if the molecule is excited to a state higher in energy than the energy barrier of the subsequent reaction process. 13,36 Table 2. The R2PI peak positions and vibrational frequencies in S1 of PBI-H2O and PBI-D2O are given in cm -1 along with the assignment.…”
Section: Structures Of Pbi-s Complexesmentioning
confidence: 99%
“…The above proceeds efficiently if the molecule is excited to a state higher in energy than the energy barrier of the subsequent reaction process. 13,36 Table 2. The R2PI peak positions and vibrational frequencies in S1 of PBI-H2O and PBI-D2O are given in cm -1 along with the assignment.…”
Section: Structures Of Pbi-s Complexesmentioning
confidence: 99%
“…The fast non-radiative decay of indigo via hopping is the most accepted mechanism of photostability. This process explains why indigo is robustly photostable in the gas phase. ,,− …”
Section: Introductionmentioning
confidence: 98%
“…This process explains why indigo is robustly photostable in the gas phase. 16,19,[24][25][26][27][28][29][30][31][32][33][34][35]…”
mentioning
confidence: 99%
“…Cis–trans isomerization around double bonds in conjugated compounds can be triggered by heat, light, or catalysts such as the addition of protons, transition metal ions, Lewis acids, and so on. Especially light-induced trans–cis photoisomerization of indigo and a variety of its derivatives has been widely studied. ,− As general conclusion from these studies, it was found that although many of the derivatives undergo double-bond isomerization in the excited state, indigo itself does not. The distinctive ingredients inhibiting photoisomerization in indigo have been suggested to be the NH···OC hydrogen bonds in the trans isomer, efficient excited-state proton transfer, and efficient nonradiative internal conversion quenching the photoisomerization channel. ,,, Indigo’s resistance to photoisomerization is key to its photostability as a pigment …”
Section: Introductionmentioning
confidence: 99%
“…The distinctive ingredients inhibiting photoisomerization in indigo have been suggested to be the NH‱‱‱ OC hydrogen bonds in the trans isomer, efficient excitedstate proton transfer, and efficient nonradiative internal conversion quenching the photoisomerization channel. 5,6,9,11 Indigo's resistance to photoisomerization is key to its photostability as a pigment. 12 As an alternative to photoisomerization, protoisomerization of indigo, i.e., trans-to-cis isomerization induced by protonation, has also been addressed.…”
Section: ■ Introductionmentioning
confidence: 99%